THE ROLE OF THE ROOMBOY IN CLEANING ROOM EQUIPMENT OF THE NOVOTEL PEKANBARU HOTEL - Sefika, Sasa; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Roomboy is the spearhead of a hotel because of the role of the roomboy in cleaning room equipment for the sake of creating comfort in a hotel room. This research was conducted at Novotel Pekanbaru, which is a city hotel under the auspices of accors hotels. This study aims to find out how the roomboy in cleaning the hotel room equipment at the novotel pekanbaru in the housekeepingÂ department with a key informant of 3 (three) roomboy. This research uses descriptive, qualitative methods, in which the researcher describes the circumstances and conditions that exist to collect research data and information using interview, observation, and documentation techniques. And the results found in this research are the role of the roomboy in cleaning room equipment, it is categorized as good, but there are some roomboy who do not know the names of the furniture / objects in the room.Â Keywords : Role, Roomboy, Cleaning